Understanding the effects of changes in banking regulations on infrastructure financing in South Africa - Mukiraine, Louis (Graduate School of Business (GSB), 2024)
South Africa is the only African member of the Basel Committee on Banking Supervision (BCBS), the body responsible for setting global prudential banking standards, and as such, has adopted Basel III regulatory standards in the Banks Act 94 of 1990 (Banks Act). This study aims to establish whether the regulatory reforms, particularly the transition from Basel II to Basel III, adversely impacted commercial banks' appetite for infrastructure financing. It also aims to determine whether the reforms increased infrastructure debt pricing for borrowers, drove up related costs borne by the banks, and whether they were implemented by the local regulator, the Prudential Authority (PA), after applying the proportionality principle as recommended by the BCBS. Finally, it recommends measures to mitigate the adverse effects of the regulatory reforms for the consideration of the regulators and banks. For this exploratory qualitative study, in-depth interviews were conducted with the heads of infrastructure finance and capital management experts from four of the five largest commercial banks in South Africa, known as the ‘Big 5' SA banks. Collectively, these five banks cover virtually the entire infrastructure debt financing sector in South Africa. Recordings of the interviews conducted on MS Teams were transcribed, and a thematic analysis based on Braun and Clarke's six-step framework was employed to analyse the qualitative data. A hybrid deductive and inductive coding approach was used, which entailed deriving codes from the philosophical framework and deriving codes directly from the qualitative data to get the benefits of both methods. The findings indicate that regulatory reforms have not adversely affected banks' appetite to finance infrastructure projects, with all the banks seeking to increase their exposure partially due to institutional investors interested in investing in infrastructure assets increasing demand. The respondent banks all noted that they have had to adapt their strategies due to the regulatory reforms, such as keeping the loans on book during the early construction and ramp-up phase and thereafter selling down the long end of the assets, which have become too expensive for banks to hold to institutional investors. Additionally, the banks have redirected their attention towards delivering a greater range of advisory services. This includes mitigating risks during the early stages and taking on the role of Lead Arranger (LA) or Mandated Lead Arranger (MLA) to organize syndicated loans. The findings indicate that the reforms have increased debt financing costs mainly due to liquidity match-funding requirements and higher regulatory capital requirements, with most of these costs, passed on to the borrower by the banks. Regulatory reforms relating to derivatives have significantly increased hedging costs for risk management in infrastructure projects. The findings also indicate that the PA may not have effectively applied the proportionality principle in adopting the Basel III reforms as they were implemented fully and, in some instances, with additional conservatism compared to the Basel III accord. The key recommendations for the regulators, particularly the PA, were to harmonise regulatory reforms across economic sectors by factoring in national priorities such as job creation and economic growth. The PA could also phase implementation of the reforms over a longer timeframe to allow banks to better adapt to the regulatory changes. Additional recommendations for the PA were to make concessions to the banks concerning infrastructure assets by relaxing some of the regulatory reforms and introducing regulations (e.g., Regulation 28 governing the assets in which pension funds can invest) to incentivise other sectors of the economy to support infrastructure investment. The PA could also consider introducing regulatory concessions enabling commercial banks to compete with their development finance institution (DFI) counterparts to make infrastructure development economical. Banks were recommended to expand their related product offering, especially those beneficial to institutional investors. It was also recommended that the bank use groupings such as the Banking Association of South Africa (BASA) to undertake credible, in-depth research to support their engagement with the regulators regarding the adverse effects of regulatory reforms prior to their local adoption.